Heritage asset management and local government accountability: The role of transparency, participation, and financial capacity - Aries Tanno; Khadijah Ath Thahirah; Anne Putri; Ratnawati Raflis (Public and Municipal Finance)
Type of the article: Research Article AbstractThis study aims to examine the interrelation between public budgeting transparency, public participation, government regulation, local government financial capacity, and public trust in shaping local government accountability in heritage asset management. The study focuses on West Sumatra, Indonesia, where local governments play a crucial role in preserving cultural heritage assets. The sample included 250 local government employees actively engaged in heritage asset management. Data were collected using a structured questionnaire between March and June 2024, with responses analyzed using WarpPLS. The study rigorously adheres to ethical principles to protect the participants and ensure the integrity of the research process. Results indicate that public budgeting transparency (β = 0.165, p = 0.003) and local government financial capacity (β = 0.143, p = 0.004) both directly and indirectly, via mediating public trust, influence local government accountability (β = 0.193, p = 0.003). Government regulation (β = –0.012, p = 0.433) was not found to have any direct significant impact on accountability. On the other hand, public trust and government regulatory systems have a strong direct relationship with local government accountability but a weak indirect relationship through public trust, which makes governance mechanisms pretty complex. Public trust plays a vital role in connecting transparency, financial resilience, and accountability to the legitimacy of enforcement and effective governance. The findings underscore the significance of integrating trust-building measures, transparency, and financial capacity for governance frameworks to ensure equitable and sustainable heritage asset management.